Corrosion resistance of hybrid films applied on tin plate: precursor solution acidified with nitric acid (ph=3) (2014)
Siloxane – poly (methylmethacrylate)-based materials are systems formed by a silicon network, to which chains of poly (methylmethacrylate) are linked by covalent bonds or by physical interactions. Their stability and adherence allow their application on substrates like tin plate in order to increase the corrosion resistance. The aim of this work is to coat tin plate with a hybrid film obtained from a sol consisting of alkoxide precursors: 3 - (trimethoxysilylpropyl) methacrylate (TMSM) and poly (methyl methacrylate) PMMA. Effect of tetraethoxysilane (TEOS) addition was evaluated. Morphology was evaluated by SEM and contact angle. Electrochemical behavior was evaluated by open circuit potential (OCP), potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Results showed that siloxane-PMMA film obtained with a higher addition of TEOS had higher thickness. However, intense densification caused by TEOS addition promoted crack formation, thereby compromising the corrosion resistance.